Critical multiculturalism and deliberative democracy - Awad, Isabel (Javnost (Ljubljana), 2011)
The discredit of multiculturalism in contemporary discussions about cultural diversity and democracy is problematic since allegations of multiculturalism's failure and undemocratic consequences are used to justify a (re)turn to assimilation throughout Western societies. Rejecting assimilationism as either desirable or inevitable, this article challenges the alleged incompatibility between multiculturalism and democracy. It makes the case for a (re)conceptualisation of both multiculturalism and democracy in ways that can provide the foundations for inclusive communication. To this end, the article endorses, first, a specific kind of multiculturalism, namely, critical multiculturalism. Critical multiculturalism defines culture instructural and relational terms, underscoring the superficiality with which multiculturalism has been deployed in Western societies. Secondly, the article examines the constraints that liberal and republican models of democracy impose on a fair politics of cultural diversity. It argues that, largely due to its communication emphasis, Habermas's deliberative democracy is particularly receptive to the demands of critical multiculturalism.
Keywords: večkulturnost; democracy; demokracija; kulturne razlike; communication; komuniciranje